Effects of adaptation to crowded larval environment on the evolution of sperm competitive ability in males of Drosophila melanogaster - Rohit Kapila; Komal Maggu; Neetika Ahlawat; Nagaraj Guru Prasad (Fly)
Two of the most important environmental factors that affect the sperm competitive ability in males are the availability of resources and the socio-sexual environment. Numerous studies have investigated the individual effects of these factors, but their combined effect on the evolution of sperm competitive ability remains untested. A crowded larval environment is unique because it simultaneously affects the fitness of the organism through both resource availability and the socio-sexual environment. In this study, we used a set of four laboratory populations of D. melanogaster, evolved under a crowded larval environment for more than 165 generations and their respective controls to investigate how the sperm competitive ability of the males is affected by a single generation of larval crowding versus evolution under a crowded larval environment for more than 165 generations. Our results show that larval crowding negatively affects the sperm defence ability of males evolved in a crowded larval environment, while it has no effect on the sperm defence ability of control males. Additionally, larval crowding negatively impacts the sperm offence ability in both control and evolved populations. Males from populations adapted to a crowded larval environment exhibit lower sperm offence ability at an older age compared to control populations.